Design of concrete-filled high strength steel tubular joints subjected to compression. (November 2018) - Li, Hai-Ting; Young, Ben
Abstract: Design of concrete-filled high strength steel tubular joints subjected to compression is examined. A numerical investigation on concrete-filled high strength steel rectangular hollow section (RHS) joints is presented in this paper. The high strength steel RHS tubes had nominal yield stresses of 700 and 900 MPa. The concrete infills had nominal concrete cylinder strengths of 35 and 100 MPa. Finite element (FE) models were developed and verified against test results, showing the capability of replicating the experimental ultimate strengths, failure modes and load-deformation histories. Upon verification, a parametric study comprised 312 FE analyses was carried out. The ultimate strengths of the concrete-filled high strength steel RHS joints obtained from the parametric study together with available test results in the literature were compared with the nominal strengths calculated from existing design provisions. It is shown that the CIDECT predictions exhibited significant scatter and generally conservative for the concrete-filled high strength steel RHS joints. However, the CIDECT predictions overestimated the strengths of concrete-filled high strength steel RHS joints with chord sidewall slenderness ratio exceeded 50. Therefore, new design rules are proposed in this study for concrete-filled high strength steel RHS joints subjected to compression. Furthermore, reliability analysis was performed to assess the design rules. Highlights: New design rules are proposed for concrete-filled high strength steel tubular joints. Finite element models of concrete-filled high strength steel tubular joints were developed. Parametric study of 312 specimens was performed. Existing concrete-filled tubular joint design provisions are also assessed.